Simulasi Kendali PID Motor DC dengan Proteksi Suhu Menggunakan MATLAB Simulink - Ari Natanael Simaremare; Desman Jonto Sinaga; Ihsan Ahmad Naipospos (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
DC motors are widely used in industrial applications, so a reliable speed control and protection system is required to prevent damage caused by excessive temperature rise. This study aims to design and simulate a DC motor speed control system based on a PID controller equipped with temperature protection using the MATLAB Simulink environment. The DC motor is represented by a low‑order transfer function model, while the PID controller is employed to keep the motor speed tracking a given setpoint. The temperature signal is modeled as a time‑varying disturbance and compared to a predefined threshold using logical blocks so that, when the temperature exceeds the limit, the protection scheme disconnects the control signal to the motor and activates an alarm indicator. Simulation results show that the PID controller can maintain the motor speed close to the setpoint under normal temperature conditions, while the protection mechanism successfully stops the motor during overheat scenarios as specified. These findings indicate that combining PID control and simple logic‑based temperature protection in Simulink can serve as an effective preliminary approach for designing motor protection systems before hardware implementation.